El desastre en la literatura centroamericana contemporánea - Andrea Pezzè (Revista Crítica de Ciências Sociais, 2016)
This article aims to analyze examples of Central American literary representations about the ravages of the latest civil wars. This goal will be achieved by studying three essential writers from this region: Horacio Castellanos Moya from El Salvador, Rodrigo Rey Rosa from Guatemala, and Franz Galich from both Guatemala and Nicaragua. These writers’ countries are now in the process of translating their traumatic experiences into a coherent linguistic structure. The theoretical underpinnings are drawn from Maurice Blanchot’s essay L’écriture du désastre (1980) as well as from studies about semantic memory and theories about social blame. The objective is to demonstrate that Central American literature in particular and Spanish-American culture in general are at a new crossroads in their style of representation of their social fabrics.